After justification: Toward a Dalit public Lutheran theology. Issue 2 (3rd June 2019) - Patta, Raj Bharath
Abstract: The aim of this article is to construct a "Dalit public Lutheran theology" as an "after‐justification" conversation, which drafts an agenda for the future of Lutheran theology in the twenty‐first century. In moving toward that construction, I first briefly explain Dalit theology, public theology, and Lutheran theology and shall discuss the rationale for a Dalit public Lutheran theology. From there I propose that Lutheran theology needs to take a contextual, post‐colonial and subaltern turn. Then I discuss the contours of Dalit public Lutheran theology by discussing one of the pivotal doctrine of Luther, "justification by grace through faith, " by engaging in a Dalit public discourse and propose "hospitality by love" as what comes after justification. Finally, I bring out the relevance of such a theology for our present‐day context. The method I employ in this article is subaltern methodology, which is to "read from below" or "read against the grain." "After justification" is understood as "beyond" the understanding of doctrine of justification, as a forward‐looking public theological understanding of justification, where it finds fecundity and validity.